Competency Development Strategies for Employees in the Context of Community Empowerment - Krishernawan, Indra; Kamar, Karnawi; Yani, Ahmad; Zen, Agustian; Jusman, Ikhsan Amar (PT. LITERASI SAINS NUSANTARA, 2024)
In this era of globalization, social, economic, and technological dynamics continue to evolve rapidly. Community empowerment is becoming increasingly crucial for enhancing well-being and sustainability. In this context, the role of employees with relevant competencies becomes pivotal in supporting community empowerment efforts. Therefore, this research aims to analyze competency development strategies for employees within the context of community empowerment. The study employs a qualitative literature review method, drawing data from Google Scholar within the timeframe of 2006-2023. The study's findings indicate that competency development strategies for employees in the context of community empowerment constitute a holistic approach that plays an integral role in achieving sustainable development goals. From identifying competency needs to implementing individual development programs, these steps form a robust foundation for realizing positive changes within the community. By empowering employees through the enhancement of skills and knowledge, organizations not only strengthen their internal capacities but also make a significant contribution to community well-being.